2005
DOI: 10.1099/vir.0.81021-0
|View full text |Cite
|
Sign up to set email alerts
|

Early endocytosis pathways in SSN-1 cells infected by dragon grouper nervous necrosis virus

Abstract: Many fish undergo betanodavirus infection. To study the infection process of dragon grouper nervous necrosis virus (DGNNV), native virus and virus-like particles (VLPs) were used to analyse the binding and internalization in SSN-1 cells. The binding of DGNNV and VLPs to SSN-1 cells was demonstrated using Western blotting and immunofluorescence microscopy. As estimated by indirect ELISA, the DGNNV particles bound SSN-1 cells in a dose-dependent manner up to 8610 4 particles per cell. The binding of VLPs was sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…The different replication behaviour of r247 + 270 in both E-11 and sole neurons could be explained by an interaction with different cell receptors. Sialic acid seems to be involved in the binding of betanodavirus to SNN-1 cells [38] and therefore also to E-11, which are a clone of SSN-1 [17]. However, in other cell lines, other NNV receptors have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The different replication behaviour of r247 + 270 in both E-11 and sole neurons could be explained by an interaction with different cell receptors. Sialic acid seems to be involved in the binding of betanodavirus to SNN-1 cells [38] and therefore also to E-11, which are a clone of SSN-1 [17]. However, in other cell lines, other NNV receptors have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SSN-1 fish cells (Frerichs et al 1996) were shown to have receptor-like molecules for RGNNV on their surfaces (Lu et al 2003). The sialic acid moiety on the receptor-like molecule is required for the binding of SSN-1 cells to virus particles (Liu et al 2005). Because SSN-1 cells are susceptible to all the 4 types of betanodaviruses (Iwamoto et al 1999), the putative receptor should be able to bind the 4 kinds of virus particles and induce viral entry into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…NNV-specific monoclonal antibodies with high neutralizing titers were developed (16), suggesting that NNV-specific receptors exist on the host cell membrane. NNV has been reported to infect cells through receptor-mediated endocytosis and macropinocytosis, and the sialic acid residue is the binding target for NNV during viral binding in susceptible SSN-1 cells (17). However, no NNVspecific receptor protein has been reported.…”
mentioning
confidence: 99%